Correction: Thermo-orientation in fluids of arbitrarily shaped particles. Issue 10 (28th February 2020) - Gardin, Andrea; Ferrarini, Alberta
Abstract : Correction for 'Thermo-orientation in fluids of arbitrarily shaped particles' by Andrea Gardin et al., Phys. Chem. Chem. Phys., 2019, 21, 104–113.